Osteopontin (SPP1) expression on gallstone formation in rabbits fed with a lithogenic diet - Abdal, Tareek Abdulqadir; Al Naemi, Raed Salim (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This research was designed to assess the influence of the administration of a lithogenic diet, hydrogen peroxide, and vitamin AD3E on rabbits’ gallstone formation and to envisage the expression of osteopontin (OPN) in their hepatic tissues. Materials and Methods: Twenty-four healthy local mature rabbits of both genders were divided into four equal groups. At the end of the feeding period, samples of blood were taken from all rabbits after they had fasted overnight to estimate the serum lipid profile. And some of the hepatic tissue has been preserved at −28°C for molecular analysis and gene expression. Results: The gallstones were formed 100% in the GIII and 50% in the GIV. The mRNA OPN expression showed a significant increase in the GIII when compared with other groups. In Groups III and II, the serum levels of total cholesterol, Triglyceride, L-C, low-density lipoprotein-choles, and VLDL-C were significantly increased when compared with GI, while in GIII, the serum level of high-density lipoprotein-cholesterol was significantly decreased when compared with GI. Conclusion: It was concluded that the expression of the mRNA OPN was increased in the hepatic tissue of gallstone-formed rabbits. J. Adv. Vet. Anim. Res., 10(2): 301–307, June 2023 http://doi.org/10.5455/javar.2023.j682